Sports medicine considerations during the COVID-19 pandemic - Mulcahey, M. K.; Gianakos, A. L.; Mercurio, A.; Rodeo, S.; Sutton, K. M. (The American Journal of Sports Medicine, 2020)
The outbreak of the novel coronavirus (COVID-19) has resulted in upward of 14 million confirmed cases and >597,000 deaths worldwide as of July 19, 2020. The current disruption in sports activities caused by COVID-19 presents a challenge to physicians, coaches, and trainers in discerning best practices for a safe return to sport. There is a distinct need to develop and adopt consistent measures for resumption of sports activities, including training and competition, in a way that places the health and well-being of athletes at the forefront while also protecting coaches, allied staff, and spectators. This article provides an overview of the effects of COVID-19 in the athletic population and presents considerations for training during the pandemic, as well as guidelines for return to sports as restrictions are lifted.